Implementasi Lesson Study dalam Meningkatkan Kompetensi Pedagogik Guru di SMA Badan Perguruan Indonesia Kota Bandung - Mulyani, Mulyani; Hanafiah, Nanang; Sukandar, Ahmad (Edukasi: Journal of Educational Research, 2022)
This paper examines the application of the lesson study method to improve the pedagogic competence of teachers at SMA BPI Bandung. This study uses a qualitative approach by applying descriptive methods. Data collection techniques in this study were conducted by means of interviews, observation, and documentation. While the data analysis technique is carried out using three stages, data reduction, data presentation, and drawing conclusions. This study found that lesson study planning in improving the pedagogic competence of BPI SMA Bandung city teachers through collaborative and sustainable learning assessments based on the principles of collegiality and mutuality, the implementation of lesson study learning was carried out using methods and media or learning aids, while in the reflection stage or evaluation of BPI SMA lesson study using the method of gathering all teachers and discussing the learning methods applied by each teacher. The purpose of this research is to know the method of applying lesson study at SMA BPI Bandung in improving the pedagogic competence of teachers.